Socialization of the Effectiveness of Village Funds to Optimize the Financial Performance of Kebun Kelapa Village - Syaula, Maya; Ananda, Geby Citra; Farried, Annisa Ilmi; Lubis, Indah Safitri (International Conference on Sciences Development and Technology, 2023)
The results of community service activities with the title